2021
DOI: 10.1093/ajhp/zxab178
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of pharmacist-led antibiotic stewardship programs in outpatient settings in the United States: A scoping review

Abstract: Purpose To provide an overview of the impact of pharmacist interventions on antibiotic prescribing and the resultant clinical outcomes in an outpatient antibiotic stewardship program (ASP) in the United States. Methods Reports on studies of pharmacist-led ASP interventions implemented in US outpatient settings published from January 2000 to November 2020 and indexed in PubMed or Google Scholar were included. Additionally, stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…8,11,28 Previous studies have evaluated educational interventions, EHR-based interventions, or evaluation of peer-to-peer feedback individually. [8][9][10][29][30][31][32][33][34] In a recent Canadian trial, sending a single peer-comparison letter to primary-care physicians in the highest quartile of antibiotic prescribers decreased overall prescribing and prolonged-duration prescribing. 28 Those letters contained recommendations and education, signed by medical leaders.…”
Section: Discussionmentioning
confidence: 99%
“…8,11,28 Previous studies have evaluated educational interventions, EHR-based interventions, or evaluation of peer-to-peer feedback individually. [8][9][10][29][30][31][32][33][34] In a recent Canadian trial, sending a single peer-comparison letter to primary-care physicians in the highest quartile of antibiotic prescribers decreased overall prescribing and prolonged-duration prescribing. 28 Those letters contained recommendations and education, signed by medical leaders.…”
Section: Discussionmentioning
confidence: 99%
“…Similar programs targeted to clinics and providers with high levels of inappropriate antibiotic use, across specialties and care settings, may prove fruitful. [34] Our surveillance identified potential areas to target for improvement. These areas include proper documentation of outside test results and reasons for non-adherence, especially when early testing is performed.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic stewardship programmes (ASPs) are aimed at reducing the incidence of antibiotic‐related adverse events and antibiotic cost and maximizing the clinical efficacy of antibiotics 1 . It has been reported that in pharmacist‐driven ASPs for adult patients, days of therapy (DOT) with antibiotics reduced and antibiotic prescription improved 2,3 . Furthermore, the inclusion of infectious diseases pharmacists or physicians in ASPs was associated with reduced total antibiotic use and exposure among in‐patients 4 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…1 It has been reported that in pharmacist-driven ASPs for adult patients, days of therapy (DOT) with antibiotics reduced and antibiotic prescription improved. 2,3 Furthermore, the inclusion of infectious diseases pharmacists or physicians in ASPs was associated with reduced total antibiotic use and exposure among in-patients. 4 Proper antibiotic use is important in neonates.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%